Decadal variability of precipitation over the Tibetan Plateau modulated by the 11-year solar cycle over the past millennium - Hu, Ying; Sun, Weiyi; Liu, Jian; Chen, Deliang; Ning, Liang; Peng, Zhenghan (Frontiers in Earth Science, 2023)
Knowledge of precipitation over the Tibetan Plateau (TP), often referred to as the ‘Asian water tower’, is crucial for water resource management, infrastructure planning, and disaster mitigation. However, the decadal variability of TP precipitation in response to the 11-year solar cycle remains unknown. Here, we used observational data obtained between 1901 and 2013, together with proxy-based reconstructions of the past five centuries, and discovered a notable summer wet condition over the central‒southern TP, accompanied by a dry condition over the southeastern TP, during peaks in the 11-year solar cycle. Using an ensemble mean of four solar-only sensitivity experiments from the Community Earth System Model Last Millennium Ensemble (CESM‒LME), we further demonstrated that the 11-year solar cycle can induce this anomalous pattern of a wet central‒southern and dry southeastern TP. The modeling results indicated that, under a solar maximum, a substantial surface warming occurs over the Asian continent, especially the TP region; this causes an anomalous TP–Indian Ocean thermal contrast, which enhances the Indian summer monsoon (ISM). The additional TP heating also enhances and causes a northward shift of the South Asian High, which further intensifies the ISM. The enhanced ISM transports water vapor to the northern Indian continent, which rises upon reaching the central‒southern TP, substantially increasing precipitation. Meanwhile, a negative Pacific Decadal Oscillation-like sea surface temperature pattern occurs under a solar maximum, leading to a large-scale anticyclonic anomaly over the Yangtze River basin, southeastern TP, and southern Japan, substantially decreasing precipitation in these regions.